Peak Performance for Student-Athletes - Richardson, Peggy; Winklemann, Andy; Nelson, Corky (My University, 1990)
The academic advisors, working with a sport psychologist, selected freshman football players as the target group for their first attempt at reinforcing the use of psycho-educational techniques across the athletic and academic dimensions. Subsequently, the football coaching staff was asked to identify three major psychological constructs they believed would lead to optimal performance in football for the forthcoming season. Based on the coaches' rankings of the perceived importance of specific constructs for athletic success, the prioritized list included goal-setting, stress management, and visualization (imagery), respectively. These constructs were then used as the focal points for a 15-week class designed to demonstrate similarities between concepts used during football practices and games and academic situation. Samples of comparable patterns were game/test, practice/homework, pregame jitters/pretest anxiety, work as a team/study in groups, and review plays in your mind/mentally rehearse important point to remember. It was hoped that academic appeal and enthusiasm could be generated for student-athletes by relying on their high motivation toward athletics. Fifteen freshman football players participated in the project. The group met four days a week for 30 minutes per day prior to a designated study-hall period. Athletic and academic pre-posttest measures were obtained using goal-setting contracts, competitive stress inventories (Sports Competition Anxiety Test-SCAT; Competitive State Anxiety Inventory-2 with cognitive, somatic, and confidence subscales-CSAI-2), confidence questionnaires (Trait-State Confidence Inventory-TSCI), and self-reports of vividness and controllability during visualization (Vealey, 1986). The same sports tests were used to evaluate academic traits by substituting academic words and phrases for the sport-related terminology. Additionally, grade point averages for fall and spring semesters were obtained. After conducting this year-long exploratory program, two conclusions were reached. First a reduction of anxiety in sport and academic settings occurred for freshman football athletes at the end of two semesters, and secondly, student-athletes preferred personal-social topics over performance-enhancement topics.
Keywords: athletic performance; academic performance; freshmen; anxiety